Estrategias pedagógicas para promover hábitos alimenticios saludables para el mejoramiento del rendimiento académico en estudiantes de segundo año de educación básica. - Morán Mendoza, Isabel Alexandra (2025)
This research addressed problems of inadequate eating habits in second year students of basic education "a and b" of the school of basic education 18 de October, located in the parish of San Camilo, Quevedo Canton. Excessive consumption of ultra-processed foods was evidenced and the omission of nutritious breakfasts negatively affected cognitive development, attention, memory, and participation. The overall objective was to identify pedagogical strategies that promote healthy eating habits to improve academic performance. A methodology with mixed approach and convergent design was applied, which integrated qualitative techniques such as interviews with teachers and observation of students, along with quantitative instruments, likert type surveys to parents. The results showed that students with healthy eating showed higher energy, concentration and academic performance, while those with poor diet showed drowsiness, low performance and poor participation. The teachers implemented active strategies such as role plays, pictograms, games, school gardens, collaborative work, although they faced limitations such as lack of time, little training in school nutrition and weak coordination with families. On the other hand, parents recognized the importance of food in learning, but showed low involvement in school activities. It was concluded that the promotion of eating habits requires an articulated action between school, family, community, supported by active methodologies, teacher training, family participation and regulation of food supply. This research provided contextualized pedagogical proposals that strengthened the integral well-being of students from an ethical, inclusive and transformative perspective, contributing to cognitive, emotional and academic development.